THE ROLE OF HOSPITAL MANAGEMENT IN RESOLUTION OF MEDICAL DISPUTES THROUGH MEDIATION PATHS IN THE HOSPITAL - Rangkutir, Rianiari; Risdawati, Irsyam; Zarzani N, T. Riza (Universitas Efarina, 2024)
The legal relationship between medical personnel and patients in carrying out their services as health workers often results in incidents where health workers intentionally or unintentionally ignore the patient's rights until a problem or dispute arises. Mediation is a means of alternative dispute resolution outside of court. Medical malpractice is an action carried out by health workers regarding evil practices or not, in the case of failure to fulfill a standard that was initially determined by the profession. Regulations regarding the resolution of medical disputes through mediation are regulated in Article 29 of Law Number 36 of 2009, there are vague norms in it where the article regulates mediation but does not clearly explain what mediation is meant to be, more specifically it does not explain the penal mediation efforts involved. results in implicit in the settings, so it needs to be researched. PP No. 47 of 2021 CHAPTER III Hospital Obligations Article 27 paragraph (1) point r states that